A Review of Outcomes and Technique for the Robotic-Assisted Laparoscopic Retroperitoneal Lymph Node Dissection for Testicular Cancer - Zeyad R. Schwen; Mohit Gupta; Phillip M. Pierorazio (Advances in Urology)
Objectives. The robotic-assisted laparoscopic retroperitoneal lymph node dissection (R-RPLND) represents a new frontier in the surgical management of testicular cancer in the realm of minimally invasive urologic oncology. We aimed to review the early outcomes as compared to the laparoscopic and open approaches as well as describe the operative technique for the R-RPLND. Materials and Methods. We reviewed all the literature related to the R-RPLND based on an electronic PubMed search up until July 2017. Results and Discussion. Encouraged by favorable early oncologic and safety outcomes for treatment of clinical stage (CS) I nonseminomatous germ cell tumor (NSGCT), the R-RPLND affords the same recovery advantages as the laparoscopic retroperitoneal lymph node dissection (L-RPLND) while offering greater dexterity, superior visualization, and a theoretically shorter learning curve for the surgeon. While R-RPLND has a promising future in the management of patients with primary and postchemotherapy NSGCT, larger and more vigorous prospective studies are needed before supplanting the open RPLND as the gold standard approach for primary low-stage NSGCT or becoming an equivalent surgical modality in the postchemotherapy setting.